Cognitive and Affective Structure of Adolescent Suicide Survivors: An Analysis Using Albert Ellis' ABC Theory - Akhmad Harum; A. As’ad Fathan; Abdullah Sinring; Suciani Latif (Bisma The Journal of Counseling, 2025)
Data from BRIN and the mass media show a high suicide rate in Indonesia, including the city of Makassar. This study focuses on adolescent survivors of suicide attempts. The research aims to examine the composition of adolescent suicide survivors in the city of Makassar. The research method used is qualitative with the type of case study research. Data were collected through interviews, observations, and documentation studies which were analyzed using qualitative analysis including data collection, reduction and presentation, as well as drawing conclusions using the help of maxqda software. The results of the study found 2 themes of the composition of suicide prevention adolescents in the city of Makassar, namely Social Interaction and Belief. Individuals who attempt suicide experience an Activating Event in the form of bullying due to negative social interactions. This event gives rise to an irrational belief that life is no longer valuable, which then has an impact on the consequences of depression and suicidal attempt behavior. It was concluded that the composition of adolescent suicide survivors in the city of Makassar consisted of 2 themes, namely social interaction and belief. This research has implications for the development of interventions in the form of preventive and curative efforts for suicide in adolescents.